Frequency of Methicillin Resistant Staphylococcus Aureus carriers in Intensive Care Unit Staff of Tertiary Care Hospitals - Hammad, Muhammad; Mahmood, Asad; Aziz, Amna; Yasir, Muhammad; Saeed, Hafiz Asad (Pakistan Armed Forces Medical Journal, 2024)
Objective: To investigate and compare the frequency of MRSA carriers among medical and surgical Intensive Care Unit staff in Tertiary Care Hospitals. Study Design: Cross-sectional comparative study. Place and Duration of Study: Department of Medicine, Two Tertiary Care Hospitals, Rawalpindi Pakistan, from Mar to May 2022. Methodology: A total of 134 ICU staff in different working shifts, including consultants, residents, nurses, paramedics, ward attendants, and sanitary workers, were subjected to nasal swabs, which were sent for culture and sensitivity. The nasal swab culture was found to be positive and negative for MRSA. Results: Out of 70 individuals from the surgical ICU, 12(17.14%) tested positive for MRSA, while 8(11.4%) out of 64 individuals from the medical ICU tested positive for MRSA (p=0.568). The overall MRSA carriage among ICU staff was found to be 14.9%. Out of these 20(14.9%) individuals, 3 were doctors, 4 nurses, 10 paramedical staff, 1 ward attendant, and 2 sanitary workers. Only 7(35%) had confirmed contact with MRSA patients within the last 2 months, and 15(11.2%) had received prior decolonization. A total of 44(32.8%) out of 134 individuals had contact with a MRSA-carrier patient in the last 2 months. 27(20.1%) individuals had received prior decolonization for MRSA carriage, with a mean duration of 5.37±4.404 months. Conclusion MRSA is an important superbug in our ICUs. With the use of prophylactic and gunshot therapies in intensive care units, these bacteria tend to acquire resistance to the anti-microbial agents, rendering our most expensive and last line of defence ineffective.